Fuentes de Energía Renovable, Recursos Energéticos Distribuidos y Almacenamiento en Colombia: una revisión de la normatividad (2020)
This paper presents the regulations on non-conventional energy resources, distributed energy resources and electricity energy storage in Colombia. Law 1715 of 2014 is the great driving force behind the development of the trends we observe today in renewable energy and energy efficiency. This law, by lifting the restriction on the sale of energy to self-producers and establishing in a single regulation the guidelines for the promotion of clean energy, the participation of consumers in the market and the implementation of mechanisms that will make it possible to develop energy efficiency, constitutes the basis on which an electrical energy policy is being built in accordance with the challenges of decarbonization and the new trends in consumer participation in the management.